2014
DOI: 10.1016/j.fob.2014.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Necrostatin‐1 protects against reactive oxygen species (ROS)‐induced hepatotoxicity in acetaminophen‐induced acute liver failure

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
96
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(106 citation statements)
references
References 44 publications
10
96
0
Order By: Relevance
“…(2) This would also explain the similarity between the findings from Dara et al and previous results using the chemical inhibitor Nec-1 in the acetaminophen model. (5) Taken together, hepatocytic RIPK1 does neither directly mediate nor indirectly modulate acute toxicity of acetaminophen in mice.…”
Section: Lpc-komentioning
confidence: 97%
“…(2) This would also explain the similarity between the findings from Dara et al and previous results using the chemical inhibitor Nec-1 in the acetaminophen model. (5) Taken together, hepatocytic RIPK1 does neither directly mediate nor indirectly modulate acute toxicity of acetaminophen in mice.…”
Section: Lpc-komentioning
confidence: 97%
“…Although ROS are formed as a natural byproduct of the normal metabolism of oxygen, and have important roles in cell signaling and homeostasis in biological conditions, excessive ROS are detrimental. Various studies have demonstrated that excessive ROS promotes necroptosis in various cell types, whereas inhibiting ROS production reduces necroptosis (13)(14)(15)(16). In addition, previous studies revealed that ROS production is augmented in AKI, and that ROS lead to renal tubular epithelium injury via inflammasome activation, mitochondrion damage and tubular epithelium apoptosis (22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…Reactive oxygen species (ROS) promote necroptosis in cardiomyocytes, liver cells, Jurkat cells and lung adenoma cells (13)(14)(15)(16). However, the effect of ROS on the necroptosis of renal tubular epithelium remains unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be linked to the direct interface of the antipsychotic drug with hepatic kupffer cells, thereby slowing down its normal functionality. The continuous deactivation of these cells may trigger irreparable liver failure 4 . The observation was supported by the investigation which reported that hepatomegaly as well as hepatitis inflammation of the liver was obvious in patients chronically exposed to antipsychotic drugs 35 .…”
Section: Discussionmentioning
confidence: 99%